Investigation on the gastrointestinal properties of ethanolic extract of Cannabis sativa through in vivo and in vitro approaches - Alae Chda; Youssef Mahou; Youssra Znata; Hinde El Fatemi; Abdellatif Boukir; Samir Ananou; Kaouakib El Abida; Rachid Bencheikh (Shahrekord University of Medical Sciences, 2023)
Introduction: For thousands of years, Cannabis sativa has been used for its medical and recreational benefits. Nowadays, there is an increasing interest in the use of C. sativa and its non-psychoactive products/effects to treat certain diseases. This study was conducted to examine the gastrointestinal effects of a sequential ethanolic fraction of C. sativa threshing residues (EFCS). Methods: In vivo and in vitro approaches were used to investigate the gastrointestinal properties of EFCS. Antidiarrheal, antibacterial, spasmodic, laxative, and antiulcer effects were tested respectively against castor oil induced diarrhea, disc diffusion method, isolated tissue preparations, charcoal transit time, and ethanol induced ulcer model. Results: EFCS induced a spasmodic effect on an isolated rabbit jejunum, which was inhibited by atropine and verapamil. Moreover, under free calcium conditions, the effect of EFCS was significantly reduced. The acute toxicity assay in female and male mice showed that EFCS was a safe product. Additionally, EFCS like loperamide presented antidiarrheal effect in mice and inhibited intestinal fluid secretions. Unlike the standard drug (loperamide), EFCS increased the motility of the intestinal transit. Furthermore, EFCS showed a protective effect against gastric ulcers induced by ethanol in mice and exhibited antimicrobial properties against Bacillus cereus strains. Conclusion: The results of this study reveal that EFCS possesses anti-diarrheal, antibacterial, spasmodic, laxative, and anti-ulcer activities. EFCS has potential therapeutic use against gastrointestinal diseases. Also, our work values the non-psychoactive products of C. sativa.